Audience Perception of Effective Communication in Nigerian Paintings - Abodunrin, Johnson Adelani (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
Artists in Nigeria perceived effective communication differently irrespective of the socio-economic status.Communication effectiveness depends largely on the understanding of the message being passed between a sender and a receiver. Painting has been used over time to express emotion and feeling to the perceiving audience. The study is audienceâ€™s perception of communication in Nigeria painting and how it varies with the socio-economic characteristics such as age, education, gender, and being professional artist or art lovers. Questionnaires were distributed and administered to examine how the status of the art audience makes or mars effective communication in painting. The inferential statistics that were employed include â€œchi-square testâ€ to test the relationship between different variables. The data were taken in ordinal form using Likertâ€™s scale, and transformed into interval data. This was done by attaching statistical weights to the responses in the order of importance which were summed up for the parametric testing. Findings show that gender factor has nothing to do with the understanding of paintings. Also, the level of education obtained by the audience does not have much to do with understanding of contemporary Nigerian painting but a better exposure to the issue concerning the stylistic development of Nigerian painting. Art practitioners must adequately be guided on stylistic trend in painting, art education should be more intensified in educational curriculum in Nigeria. The paper concludes that audience requires a better exposure to the issues concerning the stylistic development of Nigerian painting for effective communication to take place.